Fables. [04], March of the wooden soldiers - Willingham, Bill (Fables, 2004)
When Little Red Riding Hood suddenly walks through the gate between this world and the lost Fable Homelands, she's welcomed as a miraculous survivor by nearly everyone - everyone except her old nemesis, Bigby Wolf, who smells spying and subversion more than survival. But will he be able to prove his case before disaster strikes? And how will it all affect Prince Charming's upstart campaign to become the new mayor of Fabletown?